ANSWER
Step-by-step explanation
We want to find the solution to the equation:
![\sec ^2x-2=\tan ^2x](https://img.qammunity.org/2023/formulas/mathematics/college/srqeppbxdillty1343scj28dhp5600pcrz.png)
First, let us rewrite the trigonometric terms:
![(1)/(\cos^2x)-2=(\sin ^2x)/(\cos ^2x)](https://img.qammunity.org/2023/formulas/mathematics/college/hs4p4g6ikpe4p8b0acn42c2d5kn9d4ck40.png)
Multiply both sides of the equation by cos²x:
![\begin{gathered} (\cos^2x)/(\cos^2x)-2\cos ^2x=\sin ^2x \\ 1-2\cos ^2x=\sin ^2x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/y0zdz9urta662v0k205ty7zxp7ssyuvqpo.png)
We have that:
![\cos ^2x+\sin ^2x=1](https://img.qammunity.org/2023/formulas/mathematics/college/bkbuh04anlt02sqnvd0rmh0100ln008124.png)
Substitute that for 1 in the equation:
![\cos ^2x+\sin ^2x-2\cos ^2x=\sin ^2x](https://img.qammunity.org/2023/formulas/mathematics/college/o3q6egkg0546zyd149mcrti1nyeit8ph98.png)
Simplify the equation above:
![\begin{gathered} \cos ^2x-2\cos ^2x=\sin ^2x-\sin ^2x \\ \Rightarrow-\cos ^2x=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dkvkylcfww526miewsdbfaeu1zl3jy68h6.png)